Analisis Pendekatan Saintifik sebagai Indikator Berpikir Ilmiah dalam Pembelajaran Sejarah - Ofianto Ofianto; Tri Zahra Ningsih (Diakronika, 2021)
Abstract. This study aims to analyze the extent to which the concept of a scientific approach that is generally accepted for all subjects in the curriculum in Indonesia is be able to become a basis for scientific thinking in history learning. This research is descriptive quantitative research with a survey method that aims to obtain information about the scientific thinking abilities of students in schools. The research subjects consisted of 60 high school students in Indonesia. The data was collected through a written test in the form of a description. Data analysis techniques using Partial Credit Model (PCM) with the help of the Quest program. The findings of the study showed that students who were able to answer questions in category 3 were less than 50%. These data indicate that the scientific approach that applies in general to all subjects in the curriculum in Indonesia has not been able to become the basis for students' scientific thinking skills in history learning. Based on this, the authors recommend four skills in historical learning, namely historical literacy, historical thinking, historical consciousness, and historical reasoning to be the basis for scientific thinking in historical learning. Keywords: Scientific Approach, Scientific Thinking, Historical Literacy, Historical Thinking, Historical Consciousness, and Historical Reasoning Abstrak. Penelitian ini bertujuan untuk menganalisis sejauh mana konsep pendekatan ilmiah yang berlaku umum untuk semua mata pelajaran dalam kurikulum di Indonesia mampu menjadi landasan berpikir ilmiah dalam pembelajaran sejarah. Penelitian ini merupakan penelitian deskriptif kuantitatif dengan metode survey yang bertujuan untuk memperoleh informasi gambaran tentang kemapuan berpikir ilmiah siswa di sekolah. Subjek penelitian terdiri dari 60 siswa Sekolah Menengah Atas di Indonesia. Pengumpulan data dilakukan melalui tes tertulis dalam bentuk uraian. Teknik analisis data menggunakan Partial Credit Model (PCM) dengan bantuan program Quest. Temuan penelitian menunjukkan bahwa peserta didik yang mampu menjawab soal pada kategori 3 kurang dari 50%. Data tersebut mengindikasikan bahwa pendekatan ilmiah yang berlaku secara umum untuk semua mata pelajaran dalam kurikulum di Indonesia belum mampu menjadi landasan keterampilan berpikir ilmiah siswa dalam pembelajaran sejarah. Berdasarkan hal tersebut, penulis merekomendasikan empat keterampilan dalam pembelajaran sejarah yaitu historical literacy, historical thinking, historical consciousness, dan historical reasoning untuk menjadi landasan berpikir ilmiah dalam pembalajaran sejarah. Kata Kunci: Pendekatan Ilmiah, Berpikir Ilmiah, Historical Literacy, Historical Thinking, Historical Consciousness, dan Historical Reasoning.